Developing a learning-centred framework for feedback literacy. Issue 4 (18th May 2020) - Molloy, Elizabeth; Boud, David; Henderson, Michael
Abstract: There is an increasing focus on notions of feedback in which students are positioned as active players rather than recipients of information. These discussions have been either conceptual in character or have an empirical focus on designs to support learners in feedback processes. There has been little emphasis on learners' perspectives on, and experiences of, the role they play in such processes and what they need in order to benefit from feedback. This study therefore seeks to identify the characteristics of feedback literacy – that is, how students understand and can utilise feedback for their own learning – by analysing students' views of feedback processes drawing on a substantial data set derived from a study of feedback in two large universities. The analysis revealed seven groupings of learner feedback literacy, including understanding feedback purposes and roles, seeking information, making judgements about work quality, working with emotions, and processing and using information for the benefit of their future work (31 categories in total). By identifying these realised components of feedback literacy, in the form of illustrative examples, the emergent set of competencies can enable investigations of the development of feedback literacy and improve feedback designs in courses through alignment to these standards.